Comparative Anatomical and Histological Study of the pecten oculi in three species of birds that differ in their nutrition - Ameer Al-Hamdany; Hamid AL-arajee (College of Education for Pure Sciences, 2019)
The present study dealt with the anatomical and histological structure of pecten oculi in three species of birds that differ in their nutrition, these birds were Accipiter nisus, Sturnus vulgaris and Taeniopygia guttata, by using compound light microscope and five different histological stains. The result showed that, pecten oculi was in the three species of pleated type and consisted of 17 folds in Accipiter nisus, 26 folds in Sturnus vulgaris and 19 folds in Taeniopygia guttata, these folds were vary in their thickness, as they were thicker in Accipiter nisus than the other two species. The results also showed that the pecten oculi folds of the three species contains three types of blood vessels: large size, medium size and blood capillaries. The three types of vessels were differ in their diameter and their distribution between the folds of pecten oculi with in one speceis as well as they differ in the other three species. Pecten oculi also contains pigment cells as well as peripheral cells, it ends in the three birds speceis with a structure known as the bridge which is consist of connective tissue and dense pigment cells. The bridge is rich in blood vessels of different sizes. The present study concluded that the pecten oculi differ in components and anatomical features in different speceis of birds.